AN ANALYSIS OF FIGURATIVE LANGUAGE IN DAN BYRD’S SONG LYRICS ENTITLED “BOULEVARD” - Sukmono Bayu Adhi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This purpose of this study is trying to analyze the figurative languages ??and its meaning which exist in the lyric of the song “Boulevard”. It is a descriptive qualitative research where data were taken from a songs lyrics website. Data used in this research was a song lyrics entitled "Boulevard". This song was very popular in the 80s era and sung by Dan Byrd which was released in 1984. The result of this study is indicated that: there are 12 data which contain figurative languages. They consist of 12 alliterations which 2 of them are also hyperboles and one of them is an idiom. The study shows that all of figurative languages in “Boulevard” song lyrics involves alliteration type